2016
DOI: 10.1111/pce.12768
|View full text |Cite
|
Sign up to set email alerts
|

Gene mining in halophytes: functional identification of stress tolerance genes in Lepidium crassifolium

Abstract: Extremophile plants are valuable sources of genes conferring tolerance traits, which can be explored to improve stress tolerance of crops. Lepidium crassifolium is a halophytic relative of the model plant Arabidopsis thaliana, and displays tolerance to salt, osmotic and oxidative stresses. We have employed the modified Conditional cDNA Overexpression System to transfer a cDNA library from L. crassifolium to the glycophyte A. thaliana. By screening for salt, osmotic and oxidative stress tolerance through in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…In Eutrema salsugineum (a halophyte, relative of Arabidopsis , also known as Thellungiella salsuginea and formerly Thellungiella halophila ), two functional genes responding to salt or heat stress were also identified with the FOX hunting system [ 65 , 66 ]. Also, in another Brassicaceae halophytic relative of Arabidopsis , Lepidium crassifolium , the cDNA library was screened with the FOX hunting system in Arbidopsis , and the proteins GDSL-like lipase and Acyl CoA binding protein 6 were supposed to be involved in salt tolerance and osmotic stress tolerance, respectively [ 67 ]. After a decade of development, this strategy has been identified as a powerful tool for elucidating functional genomics and facilitating the discovery of useful genes in model plants or crops [ 17 , 68 , 69 ] or digging useful candidate genes from some wild plants [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eutrema salsugineum (a halophyte, relative of Arabidopsis , also known as Thellungiella salsuginea and formerly Thellungiella halophila ), two functional genes responding to salt or heat stress were also identified with the FOX hunting system [ 65 , 66 ]. Also, in another Brassicaceae halophytic relative of Arabidopsis , Lepidium crassifolium , the cDNA library was screened with the FOX hunting system in Arbidopsis , and the proteins GDSL-like lipase and Acyl CoA binding protein 6 were supposed to be involved in salt tolerance and osmotic stress tolerance, respectively [ 67 ]. After a decade of development, this strategy has been identified as a powerful tool for elucidating functional genomics and facilitating the discovery of useful genes in model plants or crops [ 17 , 68 , 69 ] or digging useful candidate genes from some wild plants [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in another Brassicaceae halophytic relative of Arabidopsis , Lepidium crassifolium , the cDNA library was screened with the FOX hunting system in Arbidopsis , and the proteins GDSL-like lipase and Acyl CoA binding protein 6 were supposed to be involved in salt tolerance and osmotic stress tolerance, respectively [ 67 ]. After a decade of development, this strategy has been identified as a powerful tool for elucidating functional genomics and facilitating the discovery of useful genes in model plants or crops [ 17 , 68 , 69 ] or digging useful candidate genes from some wild plants [ 65 , 66 , 67 ]. The functional screening and identification of genes by transgenic assays in plants is a time-consuming and costly process during the first course of cDNA library screening.…”
Section: Discussionmentioning
confidence: 99%
“…First, potential genes from halophytes can be identified and used as candidates for improving salt tolerance in glycophytes. This can be achieved either by overexpression of identified gene of interest (reviewed in Himabindu et al, ) or by random approach wherein a cDNA library from halophyte is expressed in glycophyte and then cDNA inserts are identified in lines showing increased salt tolerance (Rigo et al, ). Second, halophyte cultivation is practiced for desalinization of degraded soils (Table ) and recovery of value‐added products (Table ).…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…Random genes were transferred from L. crassifolium to A. thaliana , and it was observed that independent transgenic lines enhanced tolerance under several stress conditions (Rigó et al, 2016). Approximately 15% of functionally unknown genes were additionally expressed under salt stress compared to the non-stress conditions in M. crystallinum (Cushman and Bohnert, 2000; Kore-eda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%